Cool Excimer Laser-Assisted Angioplasty vs. Percutaneous Transluminal Angioplasty for Infrapopliteal Arterial Occlusion: A Meta-Analysis and Systematic Review - Zhou, Mi; Qi, Lixing; Gu, Yongquan (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous transluminal angioplasty (PTA) has been the conventional therapy to infrapopliteal arterial occlusion. Lately, cool excimer laser-assisted angioplasty has been proposed to be the alternate methods. We performed a systematic review and meta-analysis of prospective and retrospective cohort studies and randomized controlled trials to assess the effect of cool excimer laser-assisted angioplasty vs. tibial balloon angioplasty in patients with infrapopliteal arterial occlusion. Methods and Results We systematically searched PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL) (all up to April, 2021). All prospective and retrospective cohort studies and randomized controlled trials comparing clinical outcomes between cool excimer laser-assisted angioplasty and tibial balloon angioplasty were included. The main endpoints were amputation-free survival (AFS), primary patency (6 months and 12 months) and free from target lesion revascularization (TLR) (3 years). Secondary outcomes included the major amputation (1 year), dissection, embolization and bailout stent. We chose the effect model according to studies' heterogeneity. A total of 122 articles were found. According to inclusion criteria, 6 papers were finally selected for the detailed evaluation. Of the 6 papers, 4 were prospective cohort studies, and 2 were retrospective studies. Compared with PTA, CELA significantly increased the rate of patency (6 months: MD 13.01, 95% CI 3.12-22.90, P < 0.05; 12 months: MD 11.88 95% CI 8.38-15.37, P < 0.05) and the rate freedom from TLR (36 months: MD 7.51 95% CI 0.63-14.40, P < 0.05). There is no statistically difference of AFS, major amputation, dissection, embolization and bailout stent between CELA group and PTA group (MD −2.82, 95% CI −8.86-3.22, P = 0.36; MD −0.17, 95% CI −1.04-0.70, P = 0.39; MD 1.11, 95% CI 0.58-2.10, P = 0.75; MD 0.46, 95% CI 0.11-1.99, P = 0.30; MD 1.89, 95% CI 0.92-3.88, P = 0.09). Conclusions CELA had superior clinical (freedom from TLR) and angiographic outcomes (patency rate) for infrapopliteal arterial occlusion at the same time CELA does not have increased intervention-related complications compared to PTA. However, CELA is unable to improve the patient's limb salvage rate compared with PTA.